2018
DOI: 10.7150/ijms.28498
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Neutrophil-to-Lymphocyte Ratio Predicts Incomplete Response to Therapy in Differentiated Thyroid Cancer

Abstract: Background: Previously we have shown that an elevated baseline neutrophil-to-lymphocyte ratio (NLR) was associated with a high risk of recurrence in patients with differentiated thyroid cancer. The clinical significance of the longitudinal changes in NLR following treatment remained unestablished.Methods: Adults patients with differentiated thyroid cancer were included in the study if the follow-up NLR data at 6 to 18 months after initial treatment were available. The response to treatment was categorized as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…A desmoplastic stromal reaction can be found in larger microcarcinomas with invasion or lymph node metastases . Using the neutrophil‐to‐lymphocyte ratio (NLR) as a surrogate marker of systemic inflammation, we reported that an increased NLR may predict an incomplete response to therapy in differentiated thyroid cancer . Of interest, microcarcinoma aggressiveness is associated with specific subsets of tumor‐infiltrating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A desmoplastic stromal reaction can be found in larger microcarcinomas with invasion or lymph node metastases . Using the neutrophil‐to‐lymphocyte ratio (NLR) as a surrogate marker of systemic inflammation, we reported that an increased NLR may predict an incomplete response to therapy in differentiated thyroid cancer . Of interest, microcarcinoma aggressiveness is associated with specific subsets of tumor‐infiltrating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…36 Using the neutrophil-to-lymphocyte ratio (NLR) as a surrogate marker of systemic inflammation, we reported that an increased NLR may predict an incomplete response to therapy in differentiated thyroid cancer. 37 Of interest, microcarcinoma aggressiveness is associated with specific subsets of tumorinfiltrating lymphocytes. Infiltration of FOXP3 + regulatory T cells may mediate peripheral immune tolerance and contribute to tumor progression in papillary thyroid microcarcinomas.…”
mentioning
confidence: 99%
“…The accuracy of NLR for different cut-off values is given in Table 3. Elevated preoperative NLR has been shown to be related with incomplete response to therapy [22], poor tumor differentiation [23], lymph node invasion [24], advanced stage [25] and higher thyroglobulin values [26] in thyroid malignancies. On the other hand, in 2016, a meta-analysis of 6 prospective cohorts with 6283 differentiated thyroid cancer patients revealed no difference in NLR 6 between patients with cancer and benign nodules with a mean difference of 0.19 (95% CI: -0.09-0.46, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, adiposity is associated with a state of chronic inflammation. After the initial treatment of thyroid cancer, an increase in neutrophil-to-lymphocyte ratio suggests an incomplete response to therapy 39 . It is worth noting that bariatric surgery is associated with decreased risk of some hormone-related cancers 40 .…”
Section: Discussionmentioning
confidence: 99%